Futuristic Architecture Theme Approach to the Design of the Automotive Center Building in the City of Medan - Uci Masda'alni; Budiani, Ina Triesna (Jurnal Koridor, 2024)
Four-wheeled and two-wheeled motorized vehicles are a very important and inherent need for human life, this is very important because it makes it easier for humans to reach where they want to go. This has also contributed to the development of automotive shops in the city of Medan and in its surroundings, because this sector has a clear investment value. This is supported by the statement of the Ministry of Industry in 2021, where the investment value in the automotive industry will reach around IDR 99.16 trillion for four-wheeled vehicles and around IDR 10.05 trillion for two-wheeled vehicles. In 2020, there will be 232,259 two-wheeled motorized vehicles and 42,397 four-wheeled vehicles. This is what underlies the need for an automotive center in the city of Medan with the aim of providing convenience for the people in the city of Medan and even around it in obtaining everything related to the automotive by considering efficiency and comfort. To create a characteristic of this building using a futuristic architectural theme, where this theme gives the impression that it is always up to date or oriented towards the future. The analysis method is carried out in this design process, which will then obtain a solution in the form of a concept that is applied to the design. The output of this design is in the form of 3-dimensional drawings and working drawings. To create a distinctive characteristic, this building uses a futuristic architectural theme, where this theme gives the impression that it always keeps up with the times or is oriented towards the future. The analysis method is carried out in this design process, which will then get a solution in the form of a concept that is applied to the design. The output of this design is in the form of 3D drawings and working drawings. To create a characteristic of this building using a futuristic architectural theme, where this theme gives the impression that it is always up to date or oriented towards the future. The analysis method is carried out in this design process, which will then obtain a solution in the form of a concept that is applied to the design. The output of this design is in the form of 3-dimensional drawings and working drawings. Â